2016
DOI: 10.1093/alcalc/agw085
|View full text |Cite
|
Sign up to set email alerts
|

Does Industry-Driven Alcohol Marketing Influence Adolescent Drinking Behaviour? A Systematic Review

Abstract: AimTo systematically review evidence on the influence of specific marketing components (Price, Promotion, Product attributes and Place of sale/availability) on key drinking outcomes (initiation, continuation, frequency and intensity) in young people aged 9–17.MethodsMEDLINE, EMBASE, SCOPUS, PsychINFO, CINAHL and ProQuest were searched from inception to July 2015, supplemented with searches of Google Scholar, hand searches of key journals and backward and forward citation searches of reference lists of identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 102 publications
(179 reference statements)
1
26
0
4
Order By: Relevance
“…Systematic reviews of the international literature, including experimental and longitudinal study designs, have concluded that exposure to alcohol advertising by youth is associated with initiation of drinking, increased drinking and binge drinking. [98][99][100][101][102][103] The alcohol industry invests substantially in advertising -over £5 billion a year (15% of annual revenue) for the leading global alcohol company 104 -which is a clear indication of the importance of this strategy in boosting sales and shareholder profits. Advertising online through social media is a growth area with international reach, 105 however, nearly half of countries report no restrictions on advertising through this medium, indicating that regulation in this area is failing to keep up with technological advances.…”
Section: Key Pointsmentioning
confidence: 99%
“…Systematic reviews of the international literature, including experimental and longitudinal study designs, have concluded that exposure to alcohol advertising by youth is associated with initiation of drinking, increased drinking and binge drinking. [98][99][100][101][102][103] The alcohol industry invests substantially in advertising -over £5 billion a year (15% of annual revenue) for the leading global alcohol company 104 -which is a clear indication of the importance of this strategy in boosting sales and shareholder profits. Advertising online through social media is a growth area with international reach, 105 however, nearly half of countries report no restrictions on advertising through this medium, indicating that regulation in this area is failing to keep up with technological advances.…”
Section: Key Pointsmentioning
confidence: 99%
“…Prior reviews have focused on indices of alcohol marketing (i.e., price, promotion, product, and placement) and behavioral drinking outcomes [20], the role of digital media and its influences on adolescent drinking behavior [21, 22], and the effects of youth exposure to alcohol advertising longitudinally [23]. However, gaps in the literature remain, including whether specific demographic groups are over exposed to alcohol advertisements, mechanisms underlying how alcohol advertisements influence behavior and potential interventions geared towards reducing the effects of alcohol advertisements among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, four systematic reviews have summarised longitudinal studies on the association between exposure to alcohol marketing and youth alcohol use. The reviews, published between 2009 and 2017, collectively included 64 studies from 1994 to 2016, with participants ranging in age from nine to 29 years-old at baseline, and up to 29 years-old at follow-up (Anderson 2009a; Jernigan 2017; Scott 2017; Smith 2009). Table 1 presents key findings from the four reviews, presenting each of the studies in each review for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the four reviews investigated exposure to traditional, industry-driven marketing only (e.g. television commercials, magazine advertisements for alcoholic beverages; Jernigan 2017; Scott 2017), whereas two reviews also included influence of exposure to alcohol portrayals in the media (e.g. alcohol consumption by characters; Anderson 2009a; Smith 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation